Expropriações normativas - Freitas, Rafael Véras de (2015)
This dissertation aims to present a proposal on the legal regime of regulatory expropriation in the light of national law. It is a regulation which subtracts or minimizes the right to property, which does not follow the formal transfer of the domain to the State, without the establishment of the regulatory due process of law referred in the Article 5, item XXXIV of the Constitution of the Republic – CRFB, which requires the payment of a prior and fair compensation to expropriated. To this end, it will be investigated if the institutions through which the state intervenes in private property realize this phenomenon, or is it a failure of regulation. Finally, will be presented a proposal, de lege ferenda, of the compatibility of this phenomenon with the Brazilian Legal System.